Correlation of height with hand length and breadth in adult Kashmiri population of Baramulla district of Jammu and Kashmir - Gulzar, Shameema; Yousf, Syed Mubashir; Itoo, Mohd Saleem (International Journal of Research in Medical Sciences, 2022)
Background: Nature has designed the anatomical framework of an individual in such a way that the significant correlation between different body parts do exists which can be applied to solve the conflicts and controversies, and also there is strong ethnic and geographical variations among individuals is considered to be important assessment in identification of unknown human remains. Estimation of stature from hand dimensions which is one of the very important chapters in the field of Forensic anthropometry. Methods: This cross-sectional study was conducted amongst 200 participants (100male and 100 female) of Kashmiri population from district Baramulla of Jammu and Kashmir over a period of 4 months during 2021-22. Hand dimensions along with hand dimensions along with stature were measured instead of hand dimensions along with stature and weight were measured. Linear regression coefficient was calculated. Results: Obtained were statistically significant and showed a positive correlation between height and hand length. P value was <0.05. Conclusions: The correlation between height and hand dimensions ( length and breadth) instead of height and hand length measurements of an individual were statistically significant. This significance of correlation between the measurements can be used practically in forensic medicine to establish identity of persons in case of accidents and disasters where bodies are mutilated and body parts are fragmented.